Proses Kreatif Koreografi Karya Tari Ã¢â¬ËSuburÃ¢â¬â¢ - Maryani, Dwi (PANGGUNG, 2013)
ABSTRACTÃÂ This paper describes the creative process of choreography of fat people. It also explains that a dancer with a fat posture is not always unpleasant. A fat person is more represented, in a posi- tive way of thinking, with Ã¢â¬ÅsuburÃ¢â¬Â person. The questions to be discussed are: how is the character of dance movement of the fat people? And how is the choreography of the fat people in order to be looked beautiful and attractive? The creative process has been conducted through analyzing self dance movements and comprehending someoneÃ¢â¬â¢s painting works. The result of the study shows that dances which are performed by fat people can also be looked attractive, smooth and beautiful.ÃÂ Keywords: creative process, choreographyÃÂ ÃÂ ABSTRAKÃÂ Tulisan ini menguraikan proses kreatif koreografi orang bertubuh gemuk. Tulisan ini juga menjelaskan bahwa seorang penari bertubuh gemuk tidak selalu jelek. Orang yang gemuk,ÃÂ  dalamÃÂ  pengertianÃÂ  positif,ÃÂ  lebihÃÂ  banyakÃÂ  diartikanÃÂ  denganÃÂ  orangÃÂ  yangÃÂ  Ã¢â¬Ësubur Ã¢â¬â¢. Permasalahan yang diangkat ialah bagaimana karakter gerak tarian orang bertubuh ge- muk? Serta bagaimana koreografi orang bertubuh gemuk agar kelihatan indah dan me- narik? Proses kreatif dilakukan melalui penelaahan gerak-gerak dari diri sendiri serta pemahaman terhadap karya seni lukis seseorang. Hasil kajian menunjukkan bahwa ta- rian yang ditampilkan oleh orang gemuk bisa juga terlihat menarik, halus, dan indah.ÃÂ Kata kunci: proses kreatif, koreografiÃÂ ÃÂ